RELIGION IN FREUD’S APPROACH - Mukrimin Mukrimin (Graduate Program of Pontianak Institute of Islamic Studies, 2012)
This article aimed to examine the essence of religion by using Sigmund Freud’ psychoanalysis. It looks at the Freud’s theories: “the ontogenic” and “the phylogenenic”. The origins of religious and belief traditions, as Freud had mapped, are neurosis, precarious future, and religion’s masculine roots. Freud’s realist approach on religion brought a controversy on the study of religion, i.e., by associating his patients and order cultural phenomena (art, literature, and philosophy). His falsification over religion mad Freud as the most controversial man in his time. For Freud, the truth-value of religious doctrines does not lie within the scope of the present enquiry. It is enough for us, as Freud asserts that we have recognized them as being, in their psychological nature, illusions. Key Words: religion, Freud, philosophy, psycho-analysis.